Hubungan Pemenuhan Kebutuhan Spritualitas terhadap Kualitas Hidup pada Pasien Kanker yang Menjalani Kemoterapi - Eka Ayu Issetyaningsih; Mohammad Arifin Noor; Dwi Retno Sulistyaningsih (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Cancer is an abnormal cell growth that can attack the entire body so that complications can occur. Spiritual impacts often appear in cancer patients such as disturbances in spiritual beliefs and lead to a decrease in the patient's quality of life. The purpose of this study was to determine the relationship between the fulfillment of spiritual needs and the quality of life in cancer patients undergoing chemotherapy. This type of research uses a cross-sectional design, data collection with a questionnaire with 181 respondents using consecutive sampling. The data obtained were processed statistically using the chi square formula. Based on the results of the analysis obtained, of the 181 research respondents, 100% of respondents were women. Of all respondents, 47.0% had spiritual needs in the moderate category, and 47.5% of respondents had low quality of life. There is a relationship between the fulfillment of spiritual needs and the quality of life in cancer patients undergoing chemotherapy at the Sultan Agung Islamic Hospital, Semarang (p value <0.05).